Fabrication of multifunctional fluorescent organic nanoparticles with AIE feature through photo-initiated RAFT polymerization. Issue 47 (21st November 2017) - Jiang, Ruming; Liu, Meiying; Huang, Qiang; Huang, Hongye; Wan, Qing; Wen, Yuanqing; Tian, Jianwen; Cao, Qian-yong; Zhang, Xiaoyong; Wei, Yen
Abstract : Novel fluorescent organic nanoparticles with AIE feature have been fabricated through a catalyst-free photo-initiated RAFT polymerization. Abstract : Fluorescent organic nanoparticles (FONs) based on an aggregation-induced emission (AIE) dye have recently received increasing interest owing to their unique optical properties, water dispersibility and biocompatibility. However, fabrication of multifunctional AIE-active FONs through a facile controlled free radical polymerization method has not been reported thus far. In this work, a novel photo-initiated reversible addition–fragmentation chain-transfer (RAFT) polymerization has been developed for the fabrication of AIE-active FONs for the first time. During this procedure, a new tetraphenylethene based dye (named TPE-DETC) was conjugated to a chain transfer agent, which could serve as the fluorescence signal and catalyst for RAFT polymerization. Styrene (SE) and itaconic acid (IA) were selected as the monomers to construct the final fluorescent copolymers (TPE-SE-IA). Due to the amphiphilicity and AIE properties of TPE-DETC, the TPE-SE-IA copolymers tend to self-assemble and form FONs. The physicochemical properties, drug loading and release behavior of TPE-SE-IA FONs towards cisplatin (CDDP), their biocompatibility as well as cell uptake behavior have been investigated in detail. The results verified that TPE-SE-IA FONs possess strong fluorescence, high water dispersibility, distinguished biocompatibility and highly efficient drug loading capability, making them promising candidates for biomedical applications. More importantly, the in situ photo-initiated RAFT polymerization strategy is an ideal method to be used for the preparation of functional polymeric materials owing to its fascinating features, such as environmental friendliness, mild reaction conditions, being catalyst-free and cost effectiveness.